The effect of coaches' controlling style on the competitive anxiety of young athletes - Ramis, Y.; Torregrosa, M.; Viladrich, C.; Cruz, J. (Frontiers in Psychology, 2017)
Framed on a Self-Determination Theory perspective, the purpose of this study was to explore the predictive capacity of coaches` interpersonal controlling style on the competitive anxiety of young athletes, considering the mediating effect of the athletes` controlled motivation on this relationship. The sample consisted of 1166 athletes, aged between 9 and 18, who ranked their perceptions of coaches` controlling style, as well as the reasons for participating in sport and their competitive anxiety before or during competition. The structural models assessing both the direct effect of the controlling style on the anxiety and the complete mediated effect of the controlled motivation on this relationship revealed good fit indices. However, a significant difference of the chi-square was obtained when comparing these models to the partial mediation model, providing evidence of this last model to be more adequate to describe the relationship between coaches` controlling style and athletes` competitive anxiety. Positive significant effects of coach controlling style on the three forms of competitive anxiety were found (ßCS-SA = 0.21, p < 0.001; ßCS-W= 0.14, p < 0.001; ßCS-CD= 0.30, p < 0.001) indicating that coach controlling style could be an antecedent for athletes` anxiety in a direct way. Although this style also predicts athletes` motivation to participate, this indirect path seems to predict competitive anxiety in a less clear way. We discuss our results facing them up to Vallerand`s hierarchical model postulates, focusing on the relevant influence of coaches on the young athletes` experience in the sport context.